Graves’ disease in children with Down syndrome - Cebeci, Ayse Nurcan; Schempp, Vera; Förtsch, Katharina; Gohlke, Bettina; Marx, Martin; Dörr, Helmuth-Günther; Wölfle, Joachim (Endocrine Connections, 2024)
While subclinical or overt hypothyroidism are common in Down syndrome (DS); Graves’ disease (GD) is rare (ranges 0.6–3%). We aimed to evaluate the clinical features, course, and treatment of GD in children with DS and compare them with those without DS. Among 161 children with GD, 13 (8 female, 5 male) had DS (8%). Data were collected retrospectively from patients’ medical records. The mean age at diagnosis was 10.6 ± 4.5 years, with a female-to-male ratio 1.6:1. The main symptoms were weight loss (n = 6), increased irritability (n = 3), and increased sweating (n = 3). None had orbitopathy. Seven of 11 patients with a thyroid ultrasound at diagnosis had a goitre. On admission, all had thyroid-stimulating hormone (TSH) <0.01 mU/L (normal range (NR): 0.51–4.30), free triiodothyronine, free thyroxine (mean ± s.d.), and thyrotrophin receptor antibodies (median, range) were 22.2 ± 10.2 pmol/L (NR: 3.5–8.1), 50.2 ± 18.7 pmol/L (NR 12.6–20.9), and 17.0 (2.89–159.0) U/L (NR <1), respectively. Patients were treated either with methimazole (n = 10) or carbimazole (n = 3), a dose of 0.54 ± 0.36 mg/kg/day. The treatment was ‘block and replace’ in ten patients and ‘dose titration’ in three patients, with a mean duration of 43.4 ± 11.0 months. Of 13 patients, four are still receiving primary treatment, three are in remission, one patient had two medically treated recurrences, three underwent surgery without complications, and two patients were lost to follow-up. Our data show that the clinical course of GD in patients with DS was similar to those without DS and suggest that a prolonged medical therapy should be the preferred option.
CRIS-Team Scopus Importer:2024-06-28
Keywords: anti-thyroid drug medication; autoimmune thyroiditis; Down syndrome; Graves’ disease; hyperthyroidism